Changes in presynaptic calcium signalling accompany age‐related deficits in hippocampal LTP and cognitive impairment. Issue 5 (16th July 2019) - Pereda, Daniel; Al‐Osta, Ibrahim; Okorocha, Albert E.; Easton, Alexander; Hartell, Nicholas A.
Abstract: The loss of cognitive function accompanying healthy aging is not associated with extensive or characteristic patterns of cell death, suggesting it is caused by more subtle changes in synaptic properties. In the hippocampal CA1 region, long‐term potentiation requires stronger stimulation for induction in aged rats and mice and long‐term depression becomes more prevalent. An age‐dependent impairment of postsynaptic calcium homeostasis may underpin these effects. We have examined changes in presynaptic calcium signalling in aged mice using a transgenic mouse line (SyG37) that expresses a genetically encoded calcium sensor in presynaptic terminals. SyG37 mice showed an age‐dependent decline in cognitive abilities in behavioural tasks that require hippocampal processing including the Barnes maze, T‐maze and object location but not recognition tests. The incidence of LTP was significantly impaired in animals over 18 months of age. These effects of aging were accompanied by a persistent increase in resting presynaptic calcium, an increase in the presynaptic calcium signal following Schaffer collateral fibre stimulation, an increase in postsynaptic fEPSP slope and a reduction in paired‐pulse facilitation. These effects were not caused by synapse proliferation and were of presynaptic origin since they were evident in single presynaptic boutons. Aged synapses behaved like younger ones when the extracellular calcium concentration was reduced. Raising extracellular calcium had little effect on aged synapses but altered the properties of young synapses into those of their aged counterparts. These effects can be readily explained by an age‐dependent change in the properties or numbers of presynaptic calcium channels. Abstract : Aged mice display a cognitive impairment in hippocampal‐dependent behaviours and impaired synaptic plasticity. Using a transgenic mouse that expresses a ratiometric calcium sensor in presynaptic terminals, we show that these changes are associated with 1, age‐dependent changes in residual calcium concentration within identified presynaptic terminals and 2, increased calcium responses to activation in identified presynaptic boutons. These results indicate that changes in calcium homeostasis in presynaptic terminals contribute to age‐dependent changes in synaptic properties and hippocampal function.